MAMAN PLANT BIOACTIVE COMPOUNDS (Cleome gyandra L), DRY POWDER (SIMPLISIA) AND JORUK MAMAN - Restusari, Lily; Yaman, Elfahmi (Acta Pharmaceutica Indonesia, 2024)
Joruk Maman is a food product that has been known to contain crude fiber and lactic acid bacteria that function as probiotics. Currently, the use of Joruk Maman as an alternative medicine for chronic diseases and functional food with high nutritional value is not too much. This study aimed to determine the antioxidant activities content of bioactive compounds from of fresh and dried-plants and Joruk Maman so that the utilization of Joruk Maman can increase. This type of research was a laboratory research with quantitative descriptive method to determine the fiber content, total phenol, and antioxidant activity in fresh plants, dry powder and joruk maman. Analysis of data from phytochemical test and bioactive compounds were analyzed descriptively with the mean and standard deviation using computerized data processing software. The results of this study showed the highest crude fiber content in the maman powder sample with a percentage of 7.84%. The highest total phenol content was found in fresh maman plant extract which contained total phenol of 35.33 mg of gallic acid equivalent/g extract. The antioxidant activities of dried, fres and fermented manan (joruk manan) using DPPH method was shown with IC50 values > 1000, 276,58 dan 323,88 μg/ml repectively, while quercetin as a tandard which is predicted also found in manan gave IC50 2,06 μg/ml. And the strongest antioxidant content was obtained with an IC value of50 in the quercetin sample of 2,06 g/ml based on the DPPH method. Further study testing is needed on the antioxidant activity of the Joruk Maman plant from each plant organ including roots, flowers and seeds with other methods to determine the potential of each part.